A120 NO EVIDENCE OF A FRIDAY EFFECT ON COLONOSCOPY QUALITY OUTCOMES. (4th March 2021) - Hindi, Z; Guizzetti, L; cocco, S; Brahmania, M; Wilson, A; Yan, B; Jairath, V; Sey, M
Abstract: Background: Colonoscopy quality may be influenced by operator fatigue. Prior studies have shown lower adenoma detection rates for procedures performed at the end of the day. However, it is unknown if colonoscopy quality is impaired at the end of the work week. Aims: We investigated whether colonoscopy quality-related metrics differ at the end of the work week using the South West Ontario Colonoscopy Cohort. Methods: Between April 2017 to February 2018, 45, 510 consecutive colonoscopies from 20 academic and community hospitals in our health region were captured to form the cohort. In Canada, outpatient endoscopies are generally performed between Monday to Friday, taking Friday, or the last business day, as the last day of the work week compared to the rest of the work week. When a statutory holiday occurred on a Friday, Thursday was designated the last day of the work week. The primary outcome was adenoma detection rate (ADR), and secondary outcomes were sessile serrated polyp detection rate (ssPDR), polyp detection rate (PDR), and failed cecal intubation. Outcomes were presented as unadjusted and adjusted risk ratios derived from modified Poisson regression and adjusting for physician-level clustering, and characteristics of the patient (age, sex, severity), procedure (hospital setting, trainee presence, indication, sedation, bowel preparation quality) and physician (experience and specialty). Results: During the observation period, 9, 132 colonoscopies were performed on the last day of the work week compared to 36, 378 procedures during the rest of the work week. No significant difference was observed for ADR (26.4% vs. 26.6%, p=0.75), ssPDR (4.5% vs. 5.0%, p=0.12), PDR (44.1% vs. 43.1%, p=0.081), or failed cecal intubation (2.8% vs. 2.9%, p=0.51) for colonoscopies performed on the last day of the work week compared to the rest of the week, respectively. After adjusting for potential confounders, there were no significant differences in the ADR (RR 1.01, 95% CI [0.88, 1.15], p=0.94), ssPDR (RR 0.90, 95% CI [0.70, 1.14], p=0.38), PDR (RR 1.00, 95% CI [0.92, 1.09], p=0.94), or failed cecal intubation (RR 0.92, 95% CI [0.72, 1.18], p=0.51) for colonoscopies performed on the last day of the work week compared to the rest of week, respectively. Conclusions: Colonoscopy quality metrics, including ADR, ssPDR, PDR, and failed cecal intubation are not significantly different at the end of the week. Funding Agencies: None